KETIKA KESADARAN MULTIKULTURALISME MULAI MEMUDAR Refleksi atas Dosen Studi Agama di UIN - Hanafi, Imam (HUMANIKA, 2019)
Since the early of the 21st century, multiculturalism has become a crucial issue in educational field in Indonesia. This cannot be separated from the rise of social violences related to ethnic, religion, race and social group. Therefore, it is crucial to know how is the ability of the PTKI (Islamic Higher Educations in Indonesia) responding this issue by looking at their lecturers understanding about multiculturalism. Since the change of IAIN to UIN, it is imperative for this institution to have a multicultural paradigm of Islamic studies, to be very urgent. This research wants to know the extent of multiculturalism skills in the learning process for lecturers in the classroom. At the same time want to see the level of knowledge and awareness of lecturers about multiculturalism. The results showed that the level of understanding of the lecturers was quite good, but at the level of awareness, it was still low.